Better Students Ask More Questions.
Prove: sec^2 x - 2sec x cosx + cos^2 x = tan^2 x - sin^2 x
1 Answer | add yours
sec^2 - 2secx cosx + cos^2x = tan^2x - sin^2x
(sec x - cos x)^2 = (sec ^2 x - 1) sin^2 x
Remember, sec^2x - 1 = tan^2 x :
(sec x - cos x)^2 = tan^2 x * sin^2 x
(sec x - cos x)^2 =( tan x * sin x )^2
(sec x - cos x) =sin x * sin x / cos x
(1 - cos^2 x ) = sin^2 x
Remember, 1 - cos^2 x = sin^2 x :
sin^2 x = sin^2 x
x = x
Posted by kjcdb8er on December 3, 2010 at 8:42 AM (Answer #1)
Join to answer this question
Join a community of thousands of dedicated teachers and students.